2009
DOI: 10.1007/s11367-009-0089-1
|View full text |Cite
|
Sign up to set email alerts
|

Environmental impacts of forest production and supply of pulpwood: Spanish and Swedish case studies

Abstract: Background, aim and scope Forest operations use large amounts of energy, which must be considered when life cycle assessment (LCA) methodology is applied to forest products. Forest management practices differ considerably between countries and may also differ within a country. This paper aims to identify and compare the environmental burdens from forest operations in Sweden and Spain focused on pulpwood production and supply to pulp mills. Materials and methods To perform the analysis, the main forest plantati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(48 citation statements)
references
References 40 publications
2
43
0
3
Order By: Relevance
“…Although extensive LCA studies have been conducted on biofuel logistics, the sources [8,[17][18][19]21] were chosen based on the forest feedstock type, which makes the comparison more persuasive. As shown in Table 8, the per unit values of energy demand and GHG emissions during the harvest operation is within a reasonable range as compared to prior research [8,[17][18][19]21]. The values for transport stage show an obvious decrease.…”
Section: Sensitivity Analysis and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although extensive LCA studies have been conducted on biofuel logistics, the sources [8,[17][18][19]21] were chosen based on the forest feedstock type, which makes the comparison more persuasive. As shown in Table 8, the per unit values of energy demand and GHG emissions during the harvest operation is within a reasonable range as compared to prior research [8,[17][18][19]21]. The values for transport stage show an obvious decrease.…”
Section: Sensitivity Analysis and Discussionmentioning
confidence: 99%
“…The values for transport stage show an obvious decrease. This may be because the case study is conducted in different countries (Sweden and Spain) [18], the locations of forest feedstock in mountain areas increase hauling inputs [19], and the assumption of long transport distances [21]. Sensitivity analysis for key inputs to harvesting and transportation operations was conducted.…”
Section: Sensitivity Analysis and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cherubini and Strømman [130] found that land use and/or land use changes were included in 28 out of 94 studies on bioenergy, most often as changes in carbon stocks (e.g., [131,132]). Some papers acknowledge the importance of LULUC, but have not included this due to the immature methodology (e.g., [133]), and still, some include it as an assessment of area used without any quality judgment (e.g., [134][135][136]). Lack of clear recommendations and diverging methodological proposals might be some of the reasons for this.…”
Section: Discussionmentioning
confidence: 99%
“…LVL can be manufactured in different sizes, such as floor beams, scaffold planking, as well as the flange material for prefabricated wood I-joists. However, many researchers mentioned that the engineered wood products may lead to much higher environmental impacts during manufacturing stage mainly due to chemicals consumption in the wood preparation phase [13,14]. While some researchers believed that engineered wood building design offered significantly lower environmental impacts; others reported that when considering cradle-to-grave processes, the energy requirements of engineered products are nearly identical to concrete [15,16].…”
Section: Introductionmentioning
confidence: 99%